2020
DOI: 10.1002/cbic.202000154
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Dependent Cytotoxic Properties of Terpyridine‐Based Copper Complexes

Abstract: Five copper complexes supported by terpyridine ligands were prepared and characterized, viz. 4) and [Cu(Cltpy)2](ClO4)2 ( 5); (where Naphtpy stands for 4'-((naphthalen-2-yl)methoxy)-2,2′:6′,2′′-terpyridine and Cltpy for 4′-chloro-2,2′:6′,2′′-terpyridine). Their DNA-interaction abilities were investigated, and their cytotoxic behaviors were examined with three cells lines, namely with human ovarian carcinoma cells (A2780) and its derived cisplatin-resistant line (A2780cis), and human cervix adenocarcinoma cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Previous studies have shown that the toxicity of Cu(II) 2,2´:6´,2´´-terpyridine complexes within a cellular model is highly increased upon incubation for several days. [33] Therefore, the complexes were incubated for 44 h and, after this time, the cell viability assessed. The complexes 7-9, 11-12 Several compounds were further characterised by single crystal X-ray diffraction studies.…”
Section: Biological Evaluationmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that the toxicity of Cu(II) 2,2´:6´,2´´-terpyridine complexes within a cellular model is highly increased upon incubation for several days. [33] Therefore, the complexes were incubated for 44 h and, after this time, the cell viability assessed. The complexes 7-9, 11-12 Several compounds were further characterised by single crystal X-ray diffraction studies.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…[29,30] As a class of compounds with particular interest, complexes of the type [Cu(2,2´:6´,2´´terpyridine)(Cl)2] have been studied. The terminal extension of the ligand with piperidine, bis(2-pyridylmethyl)amine [31,32], naphthalene [33], anthracene [34] as well as diverse substituted phenyl groups [35] including their multinuclear complexes have generated cytotoxic agents against various cancer cell lines. Worthy of note, the naphthalene derivative with a labile nitrate and water molecule instead of chloride ligands, was also found to be cytotoxic against cancerous cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, a number of copper(II) and palladium(II) compounds have been investigated as potential DNA binders and/or cleavers [17,18,[23][24][25]. In a previous study, we investigated the DNA-interacting and cytotoxic properties of a dinuclear [Cu(L)Cl 2 ] 2 complex, where L is a Schiff base ligand, namely (E)-phenyl-N-((pyridin-2-yl)methylene)methanamine [26].…”
Section: Introductionmentioning
confidence: 99%